Enhanced expectancies improve movement efficiency in runners - Stoate, I.; Wulf, G.; Lewthwaite, R. (Journal of Sports Sciences, 2012)
We followed up on recent findings demonstrating that enhancing performers' expectancies can improve their performance. Specifically, we examined whether providing experienced runners with positive feedback regarding their movement efficiency would increase running efficiency. Two groups of experienced runners ran on a treadmill at 75% of their maximum oxygen consumption (VO2max) for 10 min. One group (enhanced expectancy) was provided with (fabricated) feedback about the efficiency of their running style every 2 min. A control group was not given feedback. Oxygen consumption decreased in the enhanced expectancy group across measurement times (every 2 min for 10 min), but remained the same in the control group. In addition, performance perceptions changed only in the enhanced expectancy group, indicating a perception of greater ease of running and reduced fatigue when assessed after compared with before running. Finally, positive affect increased from a pre- to a post-test in the enhanced expectancy group, in contrast to the control group. Our findings show that enhanced expectancies can have a positive effect on movement efficiency and running experience. They add to the accumulating evidence for the social-cognitive-affective-motor nature of motor performance.